El poder de mercado bajo el nuevo diseño del Pool eléctrico Español (2009)
During 2006 and 2007, by means of the Royal Decree Law 3/2006, the Royal Decree 1634/2006 and the Order ITC/400/2007, several changes were introduced in the running of the wholesale electricity market in Spain. One of the objectives of these measures was to diminish the market power in the industry. This chapter intends to measure this market power by the difference between observed wholesale market prices and estimates of competitive benchmark price. This methodology has been used previously in the United Kingdom and California (Sweeting (2007) and Boresntein et al. (2002)), but has not been used so far in the electricity generation industry in Spain. The market power is reduced in the second quarter of 2006, but it increased again in the third quarter of 2007 and reached levels similar to the ones at the beginning of 2004 (0.43)